2020
DOI: 10.3390/ma13040948
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Controlling the Technological Process of Executing Floors Made of Cement-Based Materials

Abstract: The article presents original complex methodology for the effective control of the entire process of executing floors made of cement-based materials. This methodology has been lacking in literature so far. The methodology was developed on the basis of many years of the authors’ experience, which was acquired when diagnosing the technical condition of such floors. The methodology was preceded by a synthetic summary of the most important technological and technical requirements for floors made of cement-based ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In order to reduce the occurrence of cracks, the addition of fibers is used [ 16 , 17 ]. However, it should be emphasized that using fibers instead of bar reinforcements is not effective and can be seen to be a mistake [ 18 , 19 ]. It is best to use bars for mechanical reasons and the addition of fibers for protecting against early age cracking.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the occurrence of cracks, the addition of fibers is used [ 16 , 17 ]. However, it should be emphasized that using fibers instead of bar reinforcements is not effective and can be seen to be a mistake [ 18 , 19 ]. It is best to use bars for mechanical reasons and the addition of fibers for protecting against early age cracking.…”
Section: Introductionmentioning
confidence: 99%
“…The second group of papers has been devoted to the condition assessment of concrete and cement-based materials and structures [9][10][11][12][13][14][15][16][17]. Szel ąg [9] presented a paper in which he reviewed the achievements in the field of the diagnostics of the cracking in cement composites.…”
mentioning
confidence: 99%
“…The results showed that the developed computer vision system was highly effective in automatically identifying the number of cracks and precisely pointing to their localization [11]. Sadowski et al [12] proposed a complex methodology for the effective control of the entire process of executing floors made of cement-based materials. The methodology, developed based on many years of the authors' experience, has three control stages: (i) control before starting the floor; (ii) ongoing control during the execution of the floor; (iii) control tests after finishing the execution of the floor.…”
mentioning
confidence: 99%
See 1 more Smart Citation